Exploring the relationship between travel motivations and preferred tourist attractions: A case of New Zealand and The United Kingdom - Kankhuni, Zandivuta; Ngwira, Cecilia (Ottoman, 2019)
The paper seeks to explore the role specific attractions play in bringing tourists to destinations. The paper also seeks to find out whether a destination projects itself differently to different source markets. Using content analysis, the paper applies Pearce‟s travel career pattern model and McKercher‟s attractions hierarchy framework to consider the motivations of travellers and the specificity of the attractions they seek to visit. New Zealand and the United Kingdom are used as destinations. Results indicate that less experienced tourists, mostly influenced by Pearce‟s outer layer motives, are largely attracted by specific attractions. Experienced travellers, mostly driven by Pearce‟s core motives, are interested in a range of generic attractions. Destinations project themselves differently to source markets based on the needs and the characteristics of the tourists, even though recently the destinations are moving towards promoting several generic attractions rather than focusing on a few popular attractions.